Low-dissipation edge currents without edge states - Song, Justin Chien Wen (2020)
We propose that bulk free carriers in topologically trivial multivalley insulators with nonvanishing Berry curvature can give rise to low-dissipation edge currents, which are squeezed within a distance on the order of the valley diffusion length from the edge. This happens even in the absence of edge states [topological (gapless) or otherwise], and when the bulk equilibrium carrier concentration is thermally activated across the gap. Physically, the squeezed edge current arises from the spatially inhomogeneous valley orbital magnetization that develops from valley-density accumulation near the edge. While this current possesses neither topology nor symmetry protection and, as a result, is not immune to dissipation, in clean enough devices it can mimic low-loss ballistic transport.